Recurrent mutation of IGF signalling genes and distinct patterns of genomic rearrangement in osteosarcoma. - Behjati, S; Tarpey, PS; Haase, K; Ye, H; Young, MD; Alexandrov, LB; Farndon, SJ; Collord, G; Wedge, DC; Martincorena, I; Cooke, SL; Davies, H; et al. (Nature Communications, 2017)
Osteosarcoma is a primary malignancy of bone that affects children and adults. Here, we present the largest sequencing study of osteosarcoma to date, comprising 112 childhood and adult tumours encompassing all major histological subtypes. A key finding of our study is the identification of mutations in insulin-like growth factor (IGF) signalling genes in 8/112 (7%) of cases. We validate this observation using fluorescence in situ hybridization (FISH) in an additional 87 osteosarcomas, with IGF1 receptor (IGF1R) amplification observed in 14% of tumours. These findings may inform patient selection in future trials of IGF1R inhibitors in osteosarcoma. Analysing patterns of mutation, we identify distinct rearrangement profiles including a process characterized by chromothripsis and amplification. This process operates recurrently at discrete genomic regions and generates driver mutations. It may represent an age-independent mutational mechanism that contributes to the development of osteosarcoma in children and adults alike.